Analysis of Nucleotide Variations in Genes of Iron Management in Patients of Parkinson's Disease and Other Movement Disorders - Emanuela Castiglioni; Dario Finazzi; Stefano Goldwurm; Gianni Pezzoli; Gianluca Forni; Domenico Girelli; Federica Maccarinelli; Maura Poli; Maurizio Ferrari; Laura Cremonesi; Paolo Arosio (Parkinson's Disease)
The capacity to act as an electron donor and acceptor makes iron an essential cofactor of many vital processes. Its balance in the body has to be tightly regulated since its excess can be harmful by favouring oxidative damage, while its deficiency can impair fundamental activities like erythropoiesis. In the brain, an accumulation of iron or an increase in its availability has been associated with the development and/or progression of different degenerative processes, including Parkinson's disease, while iron paucity seems to be associated with cognitive deficits, motor dysfunction, and restless legs syndrome. In the search of DNA sequence variations affecting the individual predisposition to develop movement disorders, we scanned by DHPLC the exons and intronic boundary regions of ceruloplasmin, iron regulatory protein 2, hemopexin, hepcidin and hemojuvelin genes in cohorts of subjects affected by Parkinson's disease and idiopathic neurodegeneration with brain iron accumulation (NBIA). Both novel and known sequence variations were identified in most of the genes, but none of them seemed to be significantly associated to the movement diseases of interest.